Performance Comparison of Various Web Cluster Architectures - Choi, Eunmi; Lim, Yoojin; Min, Dugki (Systems Modeling and Simulation: Theory and Applications, 2005)
This paper investigates system attributes and the corresponding performances of three Web cluster architectures, which have different traffic managers: the Alteon Web switch, the ALBM Traffic Manager, and a Linux Virtual Server. The Alteon Web switch is a hardware solution and the others provide software solutions to traffic managers that control incoming traffic in web clusters. In order to compare performances of these Web cluster architectures, we perform a set of experiments with various load scheduling algorithms by using a number of classified workloads. The experimental results compare the peak performances of the Web clusters and show the effects of workload types and load scheduling algorithms on performance trends.